Evaluation of Hearing Loss in Patients with Type 2 Diabetes Mellitus and Obesity - Malathi Nagini Priyanka Javaji, Dr. JM Harsoda (South Eastern European Journal of Public Health, 2025)
Background: According to Møller et al. (2006), auditory system diseases cause changes in function and are characterised by either increased or decreased hearing sensitivity. Previous classifications of hearing diseases are based on anatomical location and include sensorineural and conductive hearing loss. The current investigation aims to evaluate how obesity and hyperglycemia affect hearing. Aim and Objectives: To investigate the effects of hyperglycemia and obesity on hearing. Materials and Methods: At a tertiary care hospital in Vikarabad, 40 people participate in a prospective observational study. The study recruited participants with elevated blood sugar levels, obesity with a BMI of ≥25 KG/m2, and both sexes between the ages of 25 and 60. Results: Our study population consisted primarily of female patients in the age range of 25 to 40 years old. Sensorineural hearing loss is far more common in diabetic people. Conclusion: The study concludes that, in comparison to non-diabetic controls, people with diabetes mellitus had a considerably higher incidence of sensorineural hearing loss. To confirm the observed SNHL in these patients, however, more research with a larger sample size is required.